The olive knot disease as a model to study the role of interspecies bacterial communities in plant disease - Buonaurio, Roberto; Moretti, Chiaraluce; da Silva, Daniel Passos; Cortese, Chiara; Ramos, Cayo; Venturi, Vittorio (Frontiers in Plant Science, 2015)
There is an increasing interest in studying interspecies bacterial interactions in diseases of animals and plants as it is believed that the great majority of bacteria found in nature live in complex communities. Plant pathologists have thus far mainly focused on studies involving single species or on their interactions with antagonistic competitors. A bacterial disease used as model to study multispecies interactions is the olive knot disease, caused by Pseudomonas savastanoi pv. savastanoi (Psv). Knots caused by Psv in branches and other aerial parts of the olive trees are an ideal niche not only for the pathogen but also for many other plant-associated bacterial species, mainly belonging to the genera Pantoea, Pectobacterium, Erwinia and Curtobacterium. The non-pathogenic bacterial species Erwinia toletana, Pantoea agglomerans and Erwinia oleae, which are frequently isolated inside the olive knots, cooperate with Psv in modulating the disease severity. Co-inoculations of these species with Psv result in bigger knots and better bacterial colonization when compared to single inoculations. Moreover, harmless bacteria co-localize with the pathogen inside the knots, indicating the formation of stable bacterial consortia that may facilitate the exchange of quorum sensing signals and metabolites. Here we discuss the possible role of bacterial communities in the establishment and development of olive knot disease, which we believe could be taking place in many other bacterial plant diseases.